Mainstreaming the Realism Paradigm on Eradication of Corruption Through Analysis of Law (Undang-Undang) No. 19 of 2019 Concerning the Eradication of Criminal Acts of Corruption - Musyaffa, Nadhif Fadhlan; Paksi, Arie Kusuma; Moh. Nizar (Universitas Muhammadiyah Surakarta, 2023)
Through an analysis of Law No. 19 of 2019 concerning the Eradication of Criminal Acts of Corruption, this paper analyzes the paradigm adopted by the Indonesian government when formulating strategies to combat corruption. Since their inception in 1957, laws and regulations on combating corruption have changed to reflect the evolution of the problem, the causes of corruption's growth in Indonesia, the dynamics of politics and the economy, and other aspects. The formation of Indonesia's Corruption Eradication Commission (KPK) in 2003, which performs a number of tasks, was a turning point in the country's efforts to eradicate corruption. With the publication of Law No. 19 of 2019, which replaces Law No. 30 of 2002 with the eradication of criminal acts of corruption, reform was also continued. This writing aims to analyze and measure the paradigm used by the Indonesian government in making policies to eradicate corruption through the analysis of Law no. 19 of 2019. The author uses the content analysis method in analyzing the law. Analysis was carried out on three indicators; actors, authorities, and governance which represent the three paradigms; realism (state), liberalism (non-state), and constructivism (social construction). Based on the results of the analysis, it can be concluded that; Law No. 19 of 2019 is strongly influenced by the realism paradigm, and although the law is appropriate to replace the previous law, the law still has several weaknesses to be corrected and revised by the government.